Rational design of high-entropy ceramics based on machine learning – A critical review. Issue 2 (April 2023) - Zhang, Jun; Xiang, Xuepeng; Xu, Biao; Huang, Shasha; Xiong, Yaoxu; Ma, Shihua; Fu, Haijun; Ma, Yi; Chen, Hongyu; Wu, Zhenggang; Zhao, Shijun
Highlights: The machine-learning (ML) workflow for rational design of HECs is summarized. ML applications in the design of HECs are reviewed and opportunities are highlighted. The bottlenecks of present machine-learning applications are identified. Abstract: High-entropy materials provide a versatile platform for the rational design of novel candidates with exotic performances. Recently, it has been demonstrated that high-entropy ceramics (HECs), depending on their compositions, show great application potential because of their superior structural and functional properties. However, the immense phase space behind HECs significantly hinders the efficient design and exploitation of high-performance HECs through traditional trial-and-error experiments and expensive ab-initio calculations. Machine learning (ML), on the other hand, has become a popular approach to accelerate the discovery of HECs and screen HECs with exceptional properties. In this article, we review the recent progress of ML applications in discovering and designing novel HECs, including carbides, nitrides, borides, and oxides. We thoroughly discuss different ingredients that are involved in ML applications in HECs, including data collection, feature engineering, model refinement, and prediction performance improvement. We finally provide an outlook on the challenges and development directions of future ML models for HEC predictions.